Why news matters - Harris, Duchess (Harris, Duchess. News literacy., 2018)
Explores the importance of the news media, detailing the effects journalists and writers can have on entire industries. Also discusses audiences today and the different ways journalists try to reach them. Includes primary sources, sidebars, color photographs, critical thinking questions, a glossary, and further resources.